Substantial pyroelectric effect enhancement in laminated composites - Chang, Harrison Hoon Seok; Huang, Zhaorong (American Institute of Physics (AIP), 2008)
A mathematical model has been developed to determine the pyroelectric coefficient (PY coef.) enhancement through secondary pyroelectric effect, utilizing a 2-2 connectivity of the pyroelectric lead zirconate titanate (PZT) and elastic laminate layers. Based on the prediction of this analysis, laminar stainless steel (St) PZT/St structures have been fabricated and more than 100% enhancement in PY coef. has been observed in these structures. Good agreement between the theoretical and experimental results was obtained by taking into account of the stain transfer loss at the St and PZT interface.